The standard molar enthalpies of formation of PbBi12O19(s) and ϕ-Pb5Bi8O17(s) by solution calorimetry. (April 2021) - Shyamkumar, S.; Reshmi, P.R.; Muthuambika, T.; Parida, Sanjit Kumar; Ganesan, Rajesh
Highlights: Δ f H 298 o of PbBi12 O19 (s) and ϕ-Pb5 Bi8 O17 (s) were determined. Dissolution was carried out in an acid solution isoperibol calorimeter. Nitric acid (aq., 4.47 mol kg −1 ) is used as the calorimetric solvent. Abstract: The standard molar enthalpies of formation of PbBi12 O19 (s) and ϕ-Pb5 Bi8 O17 (s) at 298.15 K were determined using an isoperibol calorimeter. The enthalpies of solution of ternary compounds, namely, PbBi12 O19 (s) and ϕ-Pb5 Bi8 O17 (s) as well as stoichiometric oxide mixtures, namely, PbO(s) + 6 Bi2 O3 (s) and 5 PbO(s) + 4 Bi2 O3 (s) in HNO3 (aq., 4.47 mol kg −1 ) at T = 298.15 K were measured. Using these values, Δ f H m o (298.15 K) of PbBi12 O19 (s) and ϕ-Pb5 Bi8 O17 (s) were determined as (-3549.6 ± 23.8) kJ mol −1 and (-3239.4 ± 7.6) kJ mol −1, respectively. The given uncertainties were calculated as 2σ of the mean with 0.95 level of confidence.